2008
DOI: 10.1109/tbme.2007.912427
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CSF on EEG Sensitivity Distributions of Multilayered Head Models

Abstract: We examined how the cerebrospinal fluid (CSF) affects the distribution of electroencephalogram (EEG) measurement sensitivity. We used concentric spheres and realistic head models to investigate the difference between computed-tomography (CT) and magnetic resonance image (MRI) models that exclude the CSF layer. The cortical EEG sensitivity distributions support these phenomena and show that the CSF layer significantly influences them, thus identifying the importance of including the CSF layer inside the head vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 11 publications
3
57
0
2
Order By: Relevance
“…This shift, as discussed in Maurer et al (1998), Wallois et al (2012), and Zhu et al (2003) and confirmed by the MRI data in this study, can cause up to a 30% change in thickness in the CSF layer between the brain and skull when changing between prone and supine positions. While this approximately 1 mm shift may seem minor in terms of the size of the brain, sizes of electrodes and their location precision, etc., CSF is up to 10 times more conductive than white or gray matter, and up to 100 times more conductive than bone (Oostendorp et al, 2000;Ramon et al, 2006), so changes in this thin layer of fluid actually lead to large changes in current flow, and hence scalp potential, as pointed out in the EEG forward-modeling and source-localization literature (Ramon et al, 2004(Ramon et al, , 2006Wendel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This shift, as discussed in Maurer et al (1998), Wallois et al (2012), and Zhu et al (2003) and confirmed by the MRI data in this study, can cause up to a 30% change in thickness in the CSF layer between the brain and skull when changing between prone and supine positions. While this approximately 1 mm shift may seem minor in terms of the size of the brain, sizes of electrodes and their location precision, etc., CSF is up to 10 times more conductive than white or gray matter, and up to 100 times more conductive than bone (Oostendorp et al, 2000;Ramon et al, 2006), so changes in this thin layer of fluid actually lead to large changes in current flow, and hence scalp potential, as pointed out in the EEG forward-modeling and source-localization literature (Ramon et al, 2004(Ramon et al, , 2006Wendel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This simplicity is extended through to the ellipsoid and perturbed spheroid solutions (Nolte & Curio, 1999). However, when realistically-shaped electrodes replace the point electrode model, a numerical method is necessary to solve either the forward or inverse problem using the spherical volume conductor model (Gordon et al, 2006;Ollikainen et al, 2000;Wendel et al, 2007;Wendel, Narra, Hannula, Kauppinen & Malmivuo, 2008).…”
Section: Simple Generic Modelsmentioning
confidence: 99%
“…In Wendel, Narra, Hannula, Kauppinen & Malmivuo (2008) we previously derived the external radius for our spherical head models from transverse circumferential cephalometric (BestWigOutlet, 2005;HatsUK, 2005;TheHatSite, 2005;WigSalon, 2005;. WigSalon (2005; assesses that 92% of women have heads circumferentially measuring between 54.6 cm and 57.2 cm.…”
Section: Simple Generic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These directions are either in the radial or in the tangential. Wendel et al [12] reported the importance of the cerebrospinal fluid (CSF) in a head model construction. Baumann et al [13] measured the conductivity of the CSF from seven patients at room temperature (25°C) and human body temperature (37°C) across the frequency range of 10 Hz-10 kHz.…”
Section: Introductionmentioning
confidence: 99%